Study on the flow of wood-plastic composites in the single-screw extrusion process - Wilczyński, K.; Buziak, K.; Bartnik, M. (Polimery, 2021)
Experimental studies have been done on the flow of wood-polypropylene composite with 70 wt % wood flour loading under various processing conditions of single-screw extrusion. The plasticization and flow of the polymer were evaluated on the basis of so-called cold extrusion experiment using „Screw Pulling-out Technique”. It was stated that the flow of wood-plastic composites is essentially different from the flow of thermoplastics. The flow is accompanied by slipping at the barrel walls, screw and die surfaces, also it shows ayield stress. Melting of the composite with high wood-flour content does not proceed according to the well known Tadmor model. Based on the results of the investigations, one-dimensional model of melting has been proposed. It was stated that the modeling of wood-plastic composite extrusion process requires a different approach then that used to model the extrusion of thermoplastic polymers.